Skizzen, Entwürfe, Konzepte, Arbeitsmanuskripte, Fassungen, Revisionen: Zu Mendelssohns Arbeitsweise - Koch, Armin (Die Musikforschung, 2019)
Despite numerous studies of Felix Mendelssohn Barthody's compositional process as well as critical editions of many of his compositions, the relevant terminology is still in need of more precise definition. This applies in particular to the term "Fassung(en)" or "version(s)", which should be used to denote a self-contained and concluded state of a composition which manifests itself through dissemination, performance or publication. The present study supports this working hypothesis with several case studies and suggests a new term, "Konzept" (rough copy or preliminary concept) for a preceding compositional phase. It also argues that more precise terminology enhances our understanding of Mendelssohn's compositional process.